Wheat Straw Biochar Amendment Increases Salinity Stress Tolerance in Alfalfa Seedlings by Modulating Physiological and Biochemical Responses - Shangzhi Zhong; Pengxin Hou; Congcong Zheng; Xuechen Yang; Qibo Tao; Juan Sun (Plants)
Salinity stress is a major environmental challenge that adversely impacts the physiological and biochemical processes of pasture, consequently resulting in reduced yields and compromised quality. Biochar amendment has recently emerged as a promising strategy to alleviate the deleterious effects of salinity stress. However, the interactive influences of salinity stress and wheat straw biochar on the physiological, biochemical, and growth characteristics of alfalfa (Medicago sativa L.) remain underexplored. A factorial experiment was conducted using a randomized complete design with five salinity levels (0, 25, 50, 75, and 100 mM NaCl) and three application rates of biochar (0, 25, and 50 g kg−1) to evaluate wheat straw biochar’s potential in alleviating salinity stress in alfalfa. Results showed that salinity stress increased oxidative stress (hydrogen peroxide and malondialdehyde) and reduced chlorophyll fluorescence (maximum quantum efficiency of photosystem II by 1–27%), leading to decreasing photosynthetic parameters, thereby constraining biomass accumulation by 9–77%. Wheat straw biochar amendment under the highest salinity stress, particularly at 25 g kg−1, mitigated oxidative stress by reducing H2O2 and MDA levels by 35% and 33%, respectively, while decreasing the antioxidant enzymes activities of CAT, POD, and SOD by 47%, 42%, and 39%, respectively, compared to the control (non-biochar addition). Concurrently, biochar restored the osmoregulatory substance concentrations of proline and soluble sugar by 59% and 33%, respectively, compared to the control. Furthermore, wheat straw biochar amendment increased the net CO2 assimilation rate by 98%, thereby increasing biomass by 63%. Our study demonstrates that wheat straw biochar can contribute to protecting alfalfa against salinity stress by modulating physiological and biochemical responses. These findings demonstrate that the 25 g kg−1 wheat straw biochar application had the best performance, suggesting this amendment could be a viable strategy for improving alfalfa productivity in salt-affected soils. Future research should explore long-term field applications and the underlying mechanisms of biochar–plant–soil–plant interactions under diverse saline-alkali environments.